2006
DOI: 10.2341/06-24
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Smile Analysis by Subjective and Computerized Methods

Abstract: SUMMARYPurpose: This study compared: 1) the subjective analyses of a smile done by specialists with advanced training and by general dentists; 2) the subjective analysis of a smile, or that associated with the face, by specialists with advanced training and general dentists; 3) subjective analysis using a computerized analysis of the smile by specialists with advanced training, verifying the midline, labial line, smile line, the line between commissures and the golden proportion. Methods: The sample consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 14 publications
(32 reference statements)
2
31
0
2
Order By: Relevance
“…Our results are rather in the sense of the conclusions of Ali Fayyad et al [22] in Jordan, Basting et al [23] in Brazil, Hasanreisoglu et al [24] in Turkey, Mashid et al [25] in Iran and Paris et al [20] in France. These authors have shown that there is no relationship between the arrangement of the anterior teeth and concepts of the golden number, the golden percentage or RED proportion.…”
Section: Comparison Between the Tw Uci/ch Uci And The Golden Numbersupporting
confidence: 31%
“…Our results are rather in the sense of the conclusions of Ali Fayyad et al [22] in Jordan, Basting et al [23] in Brazil, Hasanreisoglu et al [24] in Turkey, Mashid et al [25] in Iran and Paris et al [20] in France. These authors have shown that there is no relationship between the arrangement of the anterior teeth and concepts of the golden number, the golden percentage or RED proportion.…”
Section: Comparison Between the Tw Uci/ch Uci And The Golden Numbersupporting
confidence: 31%
“…Wolfart et al (18) concluded that a most attractive range can be identified for the width-to-length ratios and tooth-totooth proportions of maxillary incisors. Basting et al (19) have stated that a smile analysis should be performed in relation to facial features to achieve a most aesthetic smile.…”
Section: Discussionmentioning
confidence: 99%
“…24 The real size of the tooth has been evaluated in the literature and has been seen positively in studies of the "Golden Proportion". 3,4,26 In other studies, these references, based on this "Golden Proportion", would be inconsistent, or valid only for a specific population. 6,8,11 In the present study, no relationship could be observed between the width of the tooth and the distance between the zygomas.…”
Section: Discussionmentioning
confidence: 99%
“…18,26 General characteristics, such as culture, biotype and personality can and must be taken into consideration for a better esthetic result. 10,25 Perhaps the key to understanding this definition of a pleasant smile would be the awareness that dentition is only part of a larger figure, and must be seen within a set of features.…”
Section: Discussionmentioning
confidence: 99%